Arab fairy tale feasts : a literary cookbook - Alrawi, Karim (Crocodile Books, 2021)
"Award-winning writer and master storyteller Karim Alrawi draws on his deep knowledge of Arab culture in creating these enchanting tales that are a feast for young imaginations. These stories take readers of every age on a delightful literary, cultural and culinary odyssey. A profusion of unforgettable characters--fishermen and date merchants, child cooks and squabbling animals, beggars and thieves, genies and ghouls, sultans and princesses--appears in the stories presented here. each tale features some aspect of food, feasting or cooking, and is followed by a recipe for a classic Arab dish. Alrawi also provides a wealth of scholarly anecdotes, illuminating many aspects of Arab culture and culinary history. Nahib Kazemi's luminous illustrations capture the magic of each tale"--Inside jacket.